Mengelola Kreativitas dan Kapabilitas: Kolaborasi dan Tata Kelola Ekosistem Ruang Pameran Rembang Ranjana: Mengelola Kreativitas dan Kapabilitas: Kolaborasi dan Tata Kelola Ekosistem Ruang Pameran Ranjana Rembang - Godham Saputro; restu lanjari; rahina nugrahani; toto haryadi (GETER : Jurnal Seni Drama, Tari dan Musik, 2026)
Cultural exhibitions have turned into active spaces of identity, creativity, and socializing in local cultural ecosystems. The purpose of this research is to find out how collaboration and governance in the Rembang Ranjana exhibition encourage creativity and develop participants' capability. A qualitative approach was used, data were generated through observation and interviews with students, teachers (and remedial education teachers), curators and community actors to document the June–August 2025 exhibition. Open, axial and selective coding thematic analysis was conducted. Findings yield three results: increased student participatory engagement, more creative output, and a re-orientation of understanding culture as a process. These results are the result of collaborative interactions and adaptive governance, which promote experiential learning and action. It indicates that deep learning works to enrich genuine experiences when engaged in artistic processes. A conceptual model of governance, collaboration and capability development in cultural arts education It also provides park judges and institutions with data information to create participatory, sustainable creative ecosystems.